L’homonationalisme n’est-il que homo ? - Noureddine Noukhkhaly (Genre, Sexualité et Société)
In order to challenge the usual ciscentrism of the LGBT category, I propose in this article to examine the heuristic scope of homonationalism and to reread its contestations in the light of trans issues. Firstly, I document the deployment of homonationalist logics and their extension beyond questions of sexuality. To do this, I look back at its conceptualisation, reception and translation in the French context. I then look at the Julia Boyer affair as an example of the trans dimension, before reporting on the consequences for non-white LGBT people, with the doubts surrounding their authenticity. These elements lead me to question the responses to homonationalism. To do so, I examine scientific and activist, anti-racist, decolonial and/or queer discourses who highlighted the refusal of coming out. In turn, I show how the specific issues of trans visibility shape the (im)possibilities of discretion, both in the family and in civil status, thereby reassessing the relevance of previous discourses.